Hypoglycemic Activity and Brine Shrimp Lethality of (7E,11E,1R,2S,3R,4R,14S)-14-Acetoxy-3,4-epoxycembra-7,11,15-triene-17,2-Olide: A Metabolite of Lobophytum crassum† - V. Krishnaraju, Alluri; V.N. Rao, Tayi; Vanisree, Mulabagal; V. Subbaraju, Gottumukkala (Asian Journal of Chemistry, 2016)
Hypoglycemic activity and brine shrimp lethality of ethyl acetate soluble fraction of Lobophytum crassum and its active constituent (7E,11E,1R,2S,3R,4R,14S)-14-acetoxy-3,4-epoxycembra-7,11,15-triene-17,2-olide were tested. Both ethyl acetate fraction and cembranoid diterpene exhibited moderate hypoglycemic activity whereas cembranoid diterpene exhibited potent activity in brine shrimp lethality assay.